2020
DOI: 10.3390/ijms21082842
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hypoxia-Inducible Factor-1α and Vascular Endothelial Growth Factor by Chrysin in a Rat Model of Choroidal Neovascularization

Abstract: Age-related macular degeneration (AMD) is a leading cause of irreversible vision loss among the elderly population. Vascular endothelial growth factor (VEGF) is essential for choroidal neovascularization (CNV) development in advanced, wet AMD. Chrysin (5,7-dihydroxyflavone) is a natural flavonoid with anti-inflammatory, anti-oxidative, and anti-angiogenic effects. We hypothesized that intravitreally injected chrysin may inhibit CNV due to its inhibitory effect on angiogenesis. To determine the effects of chrys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Though it is highly beneficial, the frequent intravitreal administration is associated with severe side-effects such as infection, bleeding, endophthalmitis, inflammation, and retinal detachment. Besides, the huge economic burden for both patients and society should not be ignored ( Ferrara et al, 2006 ; Song et al, 2020 ). Our current study offered an optional, effective, and inexpensive alternative treatment for the treatment of wet AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it is highly beneficial, the frequent intravitreal administration is associated with severe side-effects such as infection, bleeding, endophthalmitis, inflammation, and retinal detachment. Besides, the huge economic burden for both patients and society should not be ignored ( Ferrara et al, 2006 ; Song et al, 2020 ). Our current study offered an optional, effective, and inexpensive alternative treatment for the treatment of wet AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is effective in preventing and reducing neovascularization in some patients, it also has limitations including the need for frequent intravitreal injection and inducement of macular disorders. What’s more, the current therapy is expensive and a huge burden for both patients and society ( Song et al, 2020 ). Therefore, the replacement of the current therapy is in urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…Its biological characteristics have been approved by previous studies. Our previous work, as well as other scholarly works, found that chrysin can provide antioxidant, anti-inflammatory, and anti-angiogenic effects [ 13 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The results of this study allow us to have better understanding of the possible pharmacological mechanism and biological activity of chrysin in DR.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, reduces the expression of VEGF and inhibits angiogenesis. Recently, chrysin was also found to inhibit laser-induced choroidal neovascularization (CNV) and down-regulate HIF-1α and VEGF expression [ 34 ]. Integrating these results, we speculate that the inhibitory effect of chrysin on the expression of HIF-1α and VEGF in a high glucose environment may contribute to the prevention or treatment of DR.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent research suggests that chrysin may be used to treat eye diseases leading to blindness, such as macular degeneration or choroidal neovascularization [86], and also autoimmune diseases [87].…”
Section: Chrysin In Neurodegenerative and Eye Diseasesmentioning
confidence: 99%